Blood-brain barrier permeability during dopamine-induced hypertension in fetal sheep - Harris, Andrew P; Robinson, Roderick; Koehler, Raymond C; Traystman, Richard J; Gleason, Christine A (Journal of applied physiology (1985), 2001)
Departments of 1  Anesthesiology/Critical Care Medicine and 2  Pediatrics, The Johns Hopkins University, Baltimore, Maryland 21287; and 3  Department of Pediatrics, University of Washington, Seattle, Washington 98195 Dopamine is often used as a pressor agent in sick newborn infants, but an increase in arterial blood pressure could disrupt the blood-brain barrier (BBB), especially in the preterm newborn. Using time-dated pregnant sheep, we tested the hypothesis that dopamine-induced hypertension increases fetal BBB permeability and cerebral water content. Barrier permeability was assessed in nine brain regions, including cerebral cortex, caudate, thalamus, brain stem, cerebellum, and spinal cord, by intravenous injection of the small tracer molecule [ 14 C]aminoisobutyric acid at 10 min after the start of dopamine or saline infusion. We studied 23 chronically catheterized fetal sheep at 0.6 (93 days, n  = 10) and 0.9 (132 days, n  = 13) gestation. Intravenous infusion of dopamine increased mean arterial pressure from 38 ± 3 to 53 ± 5 mmHg in 93-day fetuses and from 55 ± 5 to 77 ± 8 mmHg in 132-day fetuses without a decrease in arterial O 2 content. These 40% increases in arterial pressure are close to the maximum hypertension reported for physiological stresses at these ages in fetal sheep. No significant increases in the brain transfer coefficient of aminoisobutyric acid were detected in any brain region in dopamine-treated fetuses compared with saline controls at 0.6 or 0.9 gestation. There was also no significant increase in cortical water content with dopamine infusion at either age. We conclude that a 40% increase in mean arterial pressure during dopamine infusion in normoxic fetal sheep does not produce substantial BBB disruption or cerebral edema even as early as 0.6   gestation. aminoisobutyric acid; blood pressure; cerebral edema; fetus